Determining the role of sport coaches in promoting athlete mental health: a narrative review and Delphi approach - Bissett, J. E.; Kroshus, E.; Hebard, S. (BMJ Open Sport & Exercise Medicine, 2020)
Background Coaches have the potential to support athlete mental wellness, but many are unsure what to do and concerned they may unintentionally engage in behaviours that negatively impact their athletes. Education has the potential to help coaches engage in primary, secondary and tertiary preventive behaviours related to athlete mental health; however, there exists no empirical or consensus basis for specifying the target behaviours that should be included in such education.